Study of Xuanhuang Pill in protecting against alcohol liver disease using ultra-performance liquid chromatography/time-of-flight mass spectrometry and network pharmacology - Cui, Xuejie; Du, Maobo; Wei, Kunhua; Dai, Chen; Yang, Rachel Y. H.; Zhou, Bingxue; Luo, Zhaojing; Yang, Xiaonan; Yu, Yi; Lin, Wei; Wu, Yi; Liu, Yuhong (Frontiers in Endocrinology, 2023)
Xuanhuang Pill (XHP) is a traditional Chinese medicine oral formula composed of 10 herbs. The current study demonstrated that treatment with XHP ameliorated acute alcohol-induced liver injury in mice by significantly reducing alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels as well as tiglycerides (TG) and malondialdehyde (MDA) content. Remarkably, treatment also increased superoxide dismutase (SOD) activity and glutathione (GSH) content. Utilizing ultra-performance liquid chromatography/ time of flight mass spectrometry (UPLC-QTOF/MS), 199 compounds were identified as within the make-up of the XHP. Network pharmacology analysis showed that 103 targets regulated by 163 chemical components may play an important role in the protective liver effect mediated by XHP. KEGG enrichment analysis suggest that the HIF-1, FoxO, PI3K-Akt, insulin and thyroid hormone signaling pathways are key modulators of XHP’s effects. Finally, 8 key targets including Mapk1, Mapk3, Akt1, Map2k1, Pik3ca, Pik3cg, Raf1 and Prkca were verified by molecular docking and proteomics analysis, which provide insight into the hepatoprotective effect observed with XHP treatment. In summary, these results improved upon knowledge of the chemical composition and the potential mechanisms of hepatoprotective action of oral XHP treatment, providing foundational support for this formulation as a viable therapeutic option for alcoholic liver disease.